All-in-one high energy sorghum silage compared with and without antibiotic and conventional high energy sorghum silage for feedlot steers - L.I. Smart; C.L. Drake (Kansas Agricultural Experiment Station Research Reports, 1969)
Research done here in 1967 and 1968 indicated that adding a complete supplement to forage as it was ensiled gave results equal to using soybean meal at the time of feeding. The research continued to improve the complete silage. Previous work indicated that low levels of antibiotics increased bacterial growth and improved cellulose digestion in vitro. Therefore, two levels of antibiotics were tested in all-in-one silage ensiled and fed during 1968 and 1969.
Keywords: Cattlemen' s Day; 1969; Report of progress (Kansas State University. Agricultural Experiment Station); 529; Beef; High energy; Sorghum silage; Feedlot steers; In Vitro